THE INFLUENCE OF JOB CONNECTIONS AND WORK ABILITIES ON EMPLOYEE PERFORMANCE MEDIATED BY JOB SATISFACTION AT PT. TELKOM INDONESIA MEDAN BRANCH - Simangunsong, Sayyidilaffan; Prayogi, Muhammad Andi (Proceeding International Seminar of Islamic Studies, 2024)
The purpose of this study was to examine and analyze the influence of work relatedness and work ability on employee performance mediated by job satisfaction at PT. Telkom Indonesia Medan Branch directly or indirectly. The approach used in this research is a causal approach. The population in this study is all employees of PT. Telkom Indonesia Medan Branch. The sample in this study used a saturated sample of 47 employees of PT. Telkom Indonesia Medan Branch. Data collection techniques in this study used documentation, observation, and questionnaire techniques. Data analysis techniques in this study used a quantitative approach using statistical analysis using the Auter Model Analysis test, Inner Model Analysis, and Hypothesis Testing. Data processing in this study uses the PLS (Partial Least Square) software program. The results of this study prove that directly related work, work ability, job satisfaction affect employee performance. Work relatedness, work ability affect job satisfaction